The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1155/mbd.1996.1
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of the Antitumor ComplexesNa[trans‐RuCl4(DMSO)(Im)] and Na[trans‐RuCl4(DMSO)(Ind)] WithApotransferrin: a Spectroscopic Study

Abstract: Abstract. species may be detached from these adducts by addition of excess citrate at low pH. The behavior of the investigated ruthenium(Ill) complexes with apoTf is compared with that of the recently described and stdctly related ru-im and ru-ind antitumour complexes, and discussed in the frame of general strategies of drug targeting.Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 2 publications
1
34
0
Order By: Relevance
“…(areneϭp-cymene, hexamethylbenzene and lϭcarbene or nitrogen containing heterocycles) have been tested for antibacterial and antifungal activity.The tris chelates of the ruthenium with bidentate ligands show intercalate properties with the DNA 13) and bind to Fe(III) sites of the proteins lactoferin and transferrin 14,15) and transferrin is thought to be responsible for the delivery of Ru(III) to cancer cells where it is taken up via receptor mediated endocytosis.16) Transferrin normally transports Fe(III) in the blood but is only about one third occupied by Fe(III), and so there are vacant sites available for Ru(III) binding. Another important step in the mechanism of action of Ru(III) complexes is thought to be in vivo reduction to Ru(II), 17) which is kinetically more reactive than Ru(III).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(areneϭp-cymene, hexamethylbenzene and lϭcarbene or nitrogen containing heterocycles) have been tested for antibacterial and antifungal activity.The tris chelates of the ruthenium with bidentate ligands show intercalate properties with the DNA 13) and bind to Fe(III) sites of the proteins lactoferin and transferrin 14,15) and transferrin is thought to be responsible for the delivery of Ru(III) to cancer cells where it is taken up via receptor mediated endocytosis.16) Transferrin normally transports Fe(III) in the blood but is only about one third occupied by Fe(III), and so there are vacant sites available for Ru(III) binding. Another important step in the mechanism of action of Ru(III) complexes is thought to be in vivo reduction to Ru(II), 17) which is kinetically more reactive than Ru(III).…”
mentioning
confidence: 99%
“…The tris chelates of the ruthenium with bidentate ligands show intercalate properties with the DNA 13) and bind to Fe(III) sites of the proteins lactoferin and transferrin 14,15) and transferrin is thought to be responsible for the delivery of Ru(III) to cancer cells where it is taken up via receptor mediated endocytosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transferrin is a 80 kDa blood plasma protein that transports iron into the cello As rapidly growing tumor tissues have a considerable need for iron, tumor cells have an increased amount of transferrin receptors on the cell surface. Radiolabelling experiments with 103Ru demonstrated an accumulation of a Ru(III)-transferrin adduct in the tumor of mice bearing subcutaneous EMT-6 sarcoma [171] [172],have been shown to bind to transferrin, specifically at the iron-binding defts, but also at histidine residues on the surface ofthe protein [173,174]. The transferrin-bound form ofthese complexes, prepared by preincubation with the protein, were tested in a human colon cancer cellline.…”
Section: Rutheniummentioning
confidence: 99%
“…In vitro and in vivo studies show high anticancer activity of ruthenium complexes and some of them are currently undergoing clinical trials [13,14]. It has been reported that trans- [HIm][Ru(III)Cl 4 (DMSO)(Im)] (NAMI-A) is active against tumor metastases, although this compound has a low cytotoxicity against cancer cells [15,16]. Ru(II) complexes coordinated by arene ligands also exhibit promising anticancer activity [17][18][19][20], thought to be due to the hydrophobic arene ligand which enhances the biomolecular recognition processes and transport of ruthenium through cell membranes.…”
Section: Introductionmentioning
confidence: 99%